RSS based localization techniques for zigbee wireless sensor network - Habaebi, Mohamed Hadi; Rashid, Omar Khamis; Alhareth, Zyoud; Islam, Md. Rafiqul (2014)
Wireless Sensor Networks (WSN) are implemented in wide range of applications and one of these important applications is the localization and real-time tracking. The accuracy, cost, and power consumption are the most parameter for any proposed technique. Localization in indoor environment is more challenging than outdoor since the known Global Positioning System (GPS) is not working probably. In this paper a fingerprinting method for indoor localization is proposed. Real measurements were conducted using IRIS Zigbee motes in indoor environment. Three different configurations are tested where the measurements are conducted at 0, 1 and 1.6 m height. The three dimensional scenarios show more accurate results than two dimensional one.